Optimizing the catalyst circulation ratio in a reformer with a moving bed via a combination of real and computational experiments; Catalysis in Industry; Vol. 4, iss. 4 - Gyngazova M. S. Mariya Sergeevna; Chekantsev N. V. Nikita Vitalievich; Korolenko M. V. Mikhail Vladimirovich; Ivanchina E. D. Emilia Dmitrievna; Kravtsov A. V. Anatoly Vasilyevich (2012, 2012)
Title screen